(untitled) (Research, Society and Development, 2020)
Objective: Identify and discuss the contributions of adopting complex thinking to nursing knowledge. Method: This is an integrative literature review, covering the period from 2015 to 2020, searching for the keywords “Nursing” and “Complex Thinking” and “Edgar Morin” in the LILACS and BDENF databases, with 11 articles selected. Results: Among the results, the adoption category and the contributions of complex thinking to nursing knowledge were built. It is emphasized that it is necessary to understand the complexity of health and deal with contradictions and uncertainties. This implies the creation of theoretical and methodological principles articulated with the advances in nursing as a science and profession, considering: the human person, ethics and the environment. Conclusion: The linear, deterministic vision and based on certainty, needs to be rethought and to seek the construction of models that deal with the complexity of life. This implies the construction of theoretical principles articulated with the advances in nursing as a science and profession, considering: the human person, ethics, the environment subject to variations between order, disorder and reorganization.